The Influence of Payment System, Ordering System, and Shipping System towards E-Commerce Fraud - Meiliyah Ariani; Zulhawati Zulhawati (Proceedings of AICS - Social Sciences, 2017)
This study aims to examine the influence of payment systems, ordering systems, and shipping systems to fraud e-commerce. Payment systems are measured from policies, laws, institutions, operational mechanisms payment instruments, and infrastructure. Ordering system is measured from product, price, place (website view), and promotion. The shipping system is measured from speed, accuracy, volume, and condition. The sample selection was done by using purposive sampling method. The data of this study were collected from people in Sawah Baru Tanggerang Selatan, the sample use 100 respondents with the condition that they had been online shopping at Bukalapak, 18-25 years old, 26-35 years old and 35 years old, students, students and work, work. The analysis technique used is multiple regressions in SPSS version 23. The results of this study indicate that payment system, ordering system, and shipping system takes significant and positive effect towards fraud e-commerce.